ANALISIS USAHATANI SISTEM TANAM DOUBLE ROW PADA TANAMAN UBIKAYU (Manihot esculenta) DI LAMPUNG - Robet Asnawi (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2007)
The assessment of double row planting system of cassava was aimed at solving the low productivity of cassava due to the decrease of planting area in Lampung which was changed to palm oil, rubber, and cocoa as well as to fulfill the need of tapioca/cassava flour and bio-ethanol gas. The experiment was conducted at Natar Experimental Garden in South Lampung and on farmers' land in North Lampung from November 2004 to October 2005. The double row planting system treatment was a packet of technology that uses double row planting system with a distant between rows is 80 cm and 60 cm and a space within a row is 80 cm. The experiment used a UJ-5 variety in addition to the use of 200 kg of Urea, about 150 kg of SP-36 and around 100 kg of KCl with a 5 ton cattle-manure per ha. As a comparison, an observation was carried out on conventional technology where the planting is 70 x 80 cm in addition to the use of 75 kg Urea, 50 kg SP-36, 50 kg KCl and a UJ-5 variety. The results showed that the productivity of double row planting system produces as twice many as the traditional method, as shown by 60.24 ton/ha at Natar and 53.25 ton/ha in North Lampung compared to 28.45 ton/ha and 17.56 ton/ha respectively. It is increased more than 100% compared to farmers conventional planting system. In short, the• double row planting system is more feasible and profitable at R/C of 2.55 as compared to R/C of 1.65 in farmers' conventional planting system. Although with a decrease of price up to 20% occurs it would likely to proof that the double row planting system is still feasible and profitable. Key word: double row, farming system, produktivity, Manihot esculenta   Kajian sistem tanam double row pada tanaman ubikayu bertujuan untuk mengatasi rendahnya produktivitas ubikayu di Lampung, sebagai akibat dari menurunnya luas areal ubikayu menjadi kelapa sawit, karet, dan kakao serta untuk memenuhi kebutuhan bahan baku tapioka dan bio-etanol. Kajian ini telah dilaksanakan di Kebun Percobaan. Natar, Lampung Selatan dan lahan petani di Kecamatan Abung Semuli, Lampung Utara, mulai bulan Nopember 2004 sampai Oktober 2005. Penerapan paket teknologi sistem tanam double row yakni jarak antar barisan 80 cm dan 160 cm dengan jarak dalam barisan sama yakni 80 cm. Paket ini menggunakan varietas UJ-5 dan pemupukan 200 kg Urea/ha + 150 kg SP36/ha + 100 kg KCl/ha + 5 ton pupuk kandang/ha. Sebagai pembanding dilakukan pengamatan terhadap ubikayu yang umum dilakukan petani yakni jarak tanam 70 x 80 cm, pupuk 75 kg Urea/ha + 50 kg SP36 + 50 kg KCl serta varietas UJ-5. Hasil kajian menunjukkan bahwa produktivitas ubikayu dengan teknologi petani menghasilkan 28,45 ton/ha di KP Natar dan 17,56 ton/ha di Lampung Utara, sedangkan sistem tanam double row adalah 60,24 ton/ha di KP Natar dan 53,52 ton/ha pada lahan petani di Lampung Utara atau terjadi peningkatan produktivitas lebih dari 100%. Usahatani ubikayu dengan sistem tanam double row kompetitif dan layak diusahakan dengan nilai R/C 2,55, sedangkan pada cara petani memiliki nilai R/C 1,65. Walaupun terjadi penurunan harga jual ubikayu sampai 20%, sistem tanam double row masih layak dan menguntungkan. Kata Rand: double row, usahatani, produktivitas, Manihot esculenta